Assessing left atrial function in acute decompensated heart failure: Insights from echocardiography - Niazta, Nisa Amnifolia; Karolina, Wella; Rahimah, Anna Fuji; Prasetya, Indra (Heart Science Journal, 2026)
Acute heart failure remains a major cause hospitalization, especially in older adults and is associated with mortality and frequent readmissions. Several factors associated with heart failure outcomes include left ventricular dysfuction, left atrial dysfunction, and LA enlargement. LA enlargement has been recognized as a dependable imaging marker, closely tied to adverse outcomes such as heart failure, stroke, atrial fibrillation, and mortality. LA is not merely a passive conduit for transport. LA plays an active role and responds to distension by releasing atrial natriuretic peptides. LA enlargement has been shown to correlate with poor cardiovascular prognosis. In patients experiencing acute heart failure, fluid overload and its reduction can alter LA mechanical performance. Decongestive treatment has been associated with improved LA reservoir function, which can be assessed through parameters like LA reservoir strain rate also peak atrial longitudinal strain. In more advanced heart failure—characterized by reduced left ventricular ejection fraction, increased filling pressures, then diminished cardiac output—both PALS and strain rate are often markedly impaired, reflecting significant dysfunction in LA reservoir. Evaluating left atrial function via echocardiographic techniques is proving to be a vital tool in predicting outcomes for individuals with acute decompensated heart failure. As the understanding of LA physiology evolves, its role is increasingly seen as dynamic rather than passive. Echocardiography is showing potential imaging biomarker for risk stratification and therapeutic guidance in heart failure management.